2018
DOI: 10.1007/s10999-018-9432-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-protective properties of polymer composites with nano-titanium dioxide

Abstract: The present work investigates the ablative and thermal properties of an epoxy resin which was modified with titanium dioxide nanoparticles having different size. Prepared samples were submitted to temperatures above 1900°C and tested for their thermo-protective and ablative properties. The effect of epoxy composite components on thermo-protective and ablative properties: the maximum back side temperature, and the average weight loss under intensive heat flow conditions as well as temperature distribution on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…It has not only changed the real life of human beings but also profoundly affected the ethics and morals of traditional human society. "Double-edged sword" is the proposition of the philosophy of technology [7,8].…”
Section: Promoting Research Methodology Based Onmentioning
confidence: 99%
“…It has not only changed the real life of human beings but also profoundly affected the ethics and morals of traditional human society. "Double-edged sword" is the proposition of the philosophy of technology [7,8].…”
Section: Promoting Research Methodology Based Onmentioning
confidence: 99%
“…Studies have shown that adding nano-materials to polymers increases their tensile and flexural strength as well as temperature durability (35)(36)(37)(38) . Application of nano-sized boron and its derivatives as fillers in shielding materials and studying its features relative to micro-sized particles has been one of the interesting topics in both experimental and simulation studies (39) .…”
Section: Shielding Properties Of Nano-materials Against Thermal Neutronsmentioning
confidence: 99%
“…Good protective properties in buffering of fire and thermal shock can be obtained using composite polymer coverings with typical ablative composite matrices like silicone resin (Yuan et al, 2018), phenol resins ( Kucharczyk et al, 2013;Pulci et al, 2010;Bahramian, 2013;Zhou et al, 2019) or epoxy resins (Kucharczyk, 2010;Bakar et al, 2016;Camino et al, 2005;Kucharczyk et al, 2018;Krzyżak et al, 2018;Stawarz et al, 2019) with fillers that increase the thermal stability of a composite. Pure resins are good ablative materials.…”
Section: Introductionmentioning
confidence: 99%
“…3, No. 1, 2022: 235 -247 236 et al, 2018Kucharczyk et al, 2013;Bakar et al, 2016;Camino et al, 2005;Lombardi et al, 2012;Fino et al, 2012), nanopowdwers (Stawarz et al, 2019) or fibre reinforcement ( Pulci et al, 2010;Bahramian, 2013;Kucharczyk, 2010;Xie et al, 2020;Alagar et al, 2000;Minkook et al, 2016) or reinforcing plates (Yuan et al, 2018;Fino et al, 2012;Shi et al, 2020) of high melting temperatures build a composite structure that substantially improves thermoprotective, thermomechanical (Shi et al, 2020) and mechanical (Xie et al, 2020;Bieniaś & Jakubczak, 2017) properties of a polymer ablative composite.…”
Section: Introductionmentioning
confidence: 99%